Moisture and density (MAD) from IODP Hole 389-M0106A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Moisture and density (MAD) data from discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). MAD measurements were performed on the same samples as P-wave velocity (the same sample was used for both measurements). These discrete samples were taken during the onshore phase of expedition 389, which took place between 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Where core quality allowed cylindrical plugs were drilled perpendicular to the split core surface at an interval of one sample per core (approx. every 1.5 meter). MAD properties (bulk density, dry density, grain density, water content, porosity, and void ratio) were determined from measurements of the wet and dry mass of the sampled core plugs as well as their dry volumes. Drying took place in a convection oven at 105°±5°C for 24 hours. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025